IDENTITY AND SELF-PRESENTATION IN LETTERS OF REQUEST WRITTEN BY COLLEGE STUDENTS - Maria Corazon Saturnina Aspeli Castro (International Journal of Humanity Studies (IJHS), 2018)
Participants in an interaction risk their sense of face in every action (Goffman, 1967). Requests, by definition, are face-threatening acts (Brown and Levinson, 1978). In making a request, a speaker not only threatens the hearers negative face as he impinges on the hearers claim to freedom of action; he also threatens his positive face as he exposes himself to the possibility of being denied or rejected. In order to minimize this possibility, the speaker has to present himself in such a way that the hearer would have a positive impression of him. This paper examined letters of request written by students of a university in Metro Manila for noticeable forms of self-presentation. Following Goffmans thesis (1956) that self-presentation is a tangible component of identity, this paper analyzed lexico-syntactic patterns, and impression management strategies utilized by the writers to express their communicative intention (make a request), and construct an identity deemed necessary in attaining the hearers approval.